Chirp of the single attosecond pulse generated by a polarization gating - Chang, Zenghu (My University, 2005)
The chirp of the xuv supercontinuum generated by a polarization gating is investigated by comparing three-dimensional nonadiabatic numerical simulations with classical calculations. The origin of the chirp is the dependence of the energy gain by an electron on the return time. The chirp is positive and its value is almost the same as that when a linearly polarized laser is used. Although the 250−eV-wide supercontinuum corresponds to a single attosecond pulse, the shortest duration of the pulse is limited by the chirp. By compensating the positive chirp with the negative group velocity dispersion of a Sn filter, it is predicted that a single 58−as pulse can be generated.